Crustal structure of north Peru from analysis of teleseismic receiver functions. (July 2017) - Condori, Cristobal; França, George S.; Tavera, Hernando J.; Albuquerque, Diogo F.; Bishop, Brandon T.; Beck, Susan L.
Abstract: In this study, we present results from teleseismic receiver functions, in order to investigate the crustal thickness and Vp/Vs ratio beneath northern Peru. A total number of 981 receiver functions were analyzed, from data recorded by 28 broadband seismic stations from the Peruvian permanent seismic network, the regional temporary SisNort network and one CTBTO station. The Moho depth and average crustal Vp/Vs ratio were determined at each station using the H-k stacking technique to identify the arrival times of primary P to S conversion and crustal reverberations (PpPms, PpSs + PsPms). The results show that the Moho depth correlates well with the surface topography and varies significantly from west to east, showing a shallow depth of around 25 km near the coast, a maximum depth of 55–60 km beneath the Andean Cordillera, and a depth of 35–40 km further to the east in the Amazonian Basin. The bulk crustal Vp/Vs ratio ranges between 1.60 and 1.88 with the mean of 1.75. Higher values between 1.75 and 1.88 are found beneath the Eastern and Western Cordilleras, consistent with a mafic composition in the lower crust. In contrast values vary from 1.60 to 1.75 in the extreme flanks of the Eastern and Western Cordillera indicating a felsic composition. We find a positive relationship between crustal thickness, Vp/Vs ratio, the Bouguer anomaly, and topography. These results are consistent with previous studies in other parts of Peru (central and southern regions) and provide the first crustal thickness estimates for the high cordillera in northern Peru. Highlights: New crustal thickness estimates for northern Peru show that the Eastern Cordillera is not as thick as the Western Cordillera, suggesting isostatic imbalance. High Vp/Vs ratios are observed along the Western and Eastern Cordilleras consistent with a more mafic lower crust, compared to the Forearc to the west and Amazon Craton to the east. The crustal structure of north Peru is characterized by crustal complexities and intense tectonic activity (active orogenesis, extensional and compressional processes), and these complexities are reflected in the RFs.